Comunidad de indagación como ambiente de aprendizaje: una propuesta y una apuesta. - Cruz, Iván Darío; Castro Patarroyo, Lizeth Ximena; Ojeda Suárez, Manuel Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents the results of Philosophy for / with Children (Fp / cN) as a study of educational innovation in the development of scientific thinking in rural educational institutions in the department of Boyacá, project. The proposal begins with a theoretical construction of the learning environment and a configuration of it from the perspective of the program Philosophy for Children (FpN) of the author Mathew Lipman, and the diverse adaptations to the Philosophy with Children (FcN), likewise, with the aim of designing and developing a learning environment created in the key of an inquiry community, the study took into account different documented experiences that allowed the application and evaluation as a case study of a proposal developed in the area of Ethics and Human Values ​​with sixth grade students from an educational institution in the city of Tunja. The text concludes make evident the contributions and relevance of the community of inquiry as a learning environment, hence, proposed as a possibility of curricular transformation of educational institutions